Leveraging Information and Communication Technology ( ICT ) to Foster Inclusive Economic Growth Aligned with the SDGs: A Case Study of Lasitae Village, Barru Regency - Marsuki; Musdalifa (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal